Humanização na formação dos profissionais técnicos e tecnólogos em radioterapia - Lopes, Renata Hassler (2024)
Radiotherapy, a therapeutic modality employing ionizing radiation to inhibit the growth of neoplastic cells, necessitates particular attention to the physical and emotional vulnerabilities of oncology patients, making the provision of humanized care indispensable. Within the Brazilian healthcare context, the integration of humanization practices in radiotherapy remains limited, prompting concerns about its inclusion in technological research and the pedagogical training of technicians for the effective implementation of these practices. Given the significance of this topic and the scarcity of studies that integrate humanistic approaches in radiotherapy, this study underscores a critical gap in clinical practice. Although humanized care is widely acknowledged as essential across various healthcare sectors, particularly in the treatment of complex diseases such as cancer, its integration into the training of professionals, especially radiology technicians and technologists, who play a pivotal role in radiotherapy patient care, remains insufficient. This study aims to analyze the training of these professionals in humanization and to explore the competencies required to incorporate these practices into educational frameworks. The research was conducted in three sequential phases. The first phase, qualitative in nature, involved a bibliographic and systematic review to evaluate how humanization has been addressed in field-specific research. The second phase, quantitative in nature, included a survey of radiology technicians and technologists in Rio Grande do Sul, which examined the inclusion of humanized practices in their training. Simultaneously, a curriculum analysis of technical, technologist, and radiotherapy specialization courses offered in the state was conducted. The third phase correlated the results, identifying the competencies necessary to foster humanization in both educational and clinical settings. Survey responses suggest that professionals perceive themselves as adequately prepared for humanization practices. However, the curriculum analysis revealed a notable absence of specific courses focused on humanization, palliative care, and integrative practices. This divergence raises concerns about the overall effectiveness of professional training, highlighting the need for further research and adjustments to the educational process. It is crucial to align educational curricula with contemporary healthcare demands, encouraging a more comprehensive analysis of educational strategies and the integration of technological innovations into the teaching process.